Promoting an active choice among physically inactive adults: a randomised web-based four-arm experiment - Lorraine L. Landais; Olga C. Damman; Judith G. M. Jelsma; Evert A. L. M. Verhagen; Danielle R. M. Timmermans (BMC, 2022)
Abstract Background Promoting active (i.e., conscious, autonomous, informed, and value-congruent) choices may improve the effectiveness of physical activity interventions. This web-based four-arm experimental study investigated the effect of promoting an active versus passive choice regarding physical activity on behavioural and psychological outcomes (e.g., physical activity intentions and behaviours, autonomy, commitment) among physically inactive adults. Methods Dutch inactive adults were randomized into four groups: physical activity guideline only (control group G), guideline & information (GI), guideline & active choice (GA), or guideline & active choice & action planning (GA +). GA and GA + participants were stimulated to make an active choice by weighing advantages and disadvantages of physical activity, considering personal values, and identifying barriers. GA + participants additionally completed action/coping planning exercises. Passive choice groups G and GI did not receive exercises. Self-reported behavioural outcomes were assessed by a questionnaire pre-intervention (T0, n = 564) and at 2-4 weeks follow-up (T2, n = 493). Psychological outcomes were assessed post-intervention (T1, n = 564) and at follow-up. Regression analyses compared the outcomes of groups GI, GA and GA + with group G. We also conducted sensitivity analyses and a process evaluation. Results Although promoting an active choice process (i.e., interventions GA and GA +) did not improve intention (T1) or physical activity (T2 versus T0), GA + participants reported higher commitment at T1 (β = 0.44;95%CI:0.04;0.84) and more frequently perceived an increase in physical activity between T0 and T2 (β = 2.61;95%CI:1.44;7.72). GA participants also made a more active choice at T1 (β = 0.16;95%CI:0.04;0.27). The GA and GA + intervention did not significantly increase the remaining outcomes. GI participants reported higher intention strength (β = 0.64;95%CI:0.15;1.12), autonomy (β = 0.50;95%CI:0.05;0.95), and commitment (β = 0.39;95%CI:0.04;0.74), and made a more active choice at T1 (β = 0.13;95%CI:0.02;0.24). Interestingly, gender and health condition modified the effect on several outcomes. The GA + intervention was somewhat more effective in women. The process evaluation showed that participants varied in how they perceived the intervention. Conclusions There is no convincing evidence of a beneficial effect of an active versus passive choice intervention on physical activity intentions and behaviours among inactive adults. Further research should determine whether and how active choice interventions that are gender-sensitized and consider health conditions can effectively increase physical activity. Trial registration ClinicalTrials.gov: NCT04973813 . Retrospectively registered.